LGG-18. Inhibition of Bcl-xL targets the senescent compartment of pilocytic astrocytoma. (3rd June 2022) - Selt, Florian; Sigaud, Romain; Valinciute, Gintvile; Sievers, Philipp; Zaman, Julia; Alcon, Clara; Peterziel, Heike; Tsai, Jessica W; Guiho, Romain; Martínez-Barbera, Juan Pedro; Pusch, Stefan; Schuhmann, Martin U; et al.
Abstract: INTRODUCTION: Pilocytic astrocytoma (PA) is a mitogen-activated protein kinase (MAPK)-driven disease. Treatment of sub-totally resected PA remains challenging and relapses occur even after MAPK-targeted therapies such as MEK inhibition. Oncogenic activation of the MAPK-pathway drives the majority of cells into oncogene-induced senescence (OIS). OIS might represent a complementary vulnerability exploitable by senolytic agents. Here we investigated the senolytic properties of BH3-mimetics in PA. METHODS: Four patient-derived PA cell lines, DKFZ-BT66, -BT308, -BT317 (KIAA1549:BRAF-fusion) and DKFZ-BT314 (BRAF V600E-mutation) were treated with different BH3-mimetics, chemotherapeutics and MEK-inhibitors in proliferation (expression of SV40 large T (TAg)) and OIS (repression of TAg) states. Inhibition of metabolic activity (CellTiterGlo® 2.0) and reduction of viability (trypan blue) was assessed after 72 hours. Target expression was determined using gene expression data and Western blot. On-target activity was verified by immunoprecipitation. Dependence on Bcl-xL was investigated by shRNA-mediated knockdown and BH3-profiling. Gene expression data of primary PA and 751 cancer cell lines (GDSC dataset) was analyzed. RESULTS: BH3-mimetics inhibiting Bcl-xL (Bcl-xLi; Navitoclax, A-1131852, A-1155463, AZD4320) showed activity in 3/4 models (DKFZ-BT66, -BT314 and -BT317) in the OIS state (IC50 s <300nM). Other BH3-mimetics, chemotherapeutics and MEK-inhibitors had no effect on all models in OIS. Bcl-xL mRNA expression levels were similar, on-target activity and dependence on Bcl-xL protein was comparable in all models. Bcl-xLi-resistance of DKFZ-BT308 was linked to upregulation of genes of the HALLMARK_XENOBIOTICS_METABOLISM gene set involved in drug metabolism. Correlation of these genes with IC50 s of navitoclax was validated in an independent dataset (GDSC). CONCLUSION: Treatment with Bcl-xLi is a promising strategy targeting the senescent part of PA. IC50 s of the clinically available drug navitoclax were >20-fold below achievable plasma concentration indicating translatability. Genes from the gene set HALLMARK_XENOBIOTICS_METABOLISM could represent a predictive biomarker.